ANALISIS KAPASITAS DAYA DUKUNG PONDASI DANGKAL BERDASARKAN PENGUJIAN CONE PENETRATION TEST - Undayani Cita Sari; Nur Fithriani Fatma Cholida; Moh Nur Sholeh; M Mirza Pratama (Universitas Kristen Maranatha, 2022)
In the simple buildings, shallow foundations can be used to support the construction above them. This shallow foundation has various types, including the type of footplate which can be calculated using the Terzaghi equation. In the Terzaghi equation, it requires dimension parameters of the footing and soil material parameters such as cohesion and soil volume weight which requires laboratory testing to obtain it. Meanwhile, Schmertmann provides an equation to obtain the Terzaghi bearing capacity factor in the form of Nq and Nγ by using the Cone Penetration Test (CPT). This bearing capacity factor value can be used to calculate the bearing capacity using the Terzaghi Equation. In addition, Schmertmann also provides an equation to directly calculate the bearing capacity value based on CPT data. Based on this problem, this study analyzes the bearing capacity of various footplate dimensions using the Schmertmann approach. The study took place in the Argoboga, Salatiga which the type of soil based on the CPT test value generally is sandy soil. The results show that the bearing capacity calculated by the Nq correlation method is greater than the Nγ correlation method and the direct correlation method. In addition, the greater the difference between the dimensions and the depth of the foundation, the greater the deviation of the bearing capacity results between each method.